2019
DOI: 10.3389/fevo.2019.00016
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Positive Deviants in Western Chimpanzee Populations

Abstract: Heinicke et al. Positive Deviants in Chimpanzee Populations social-ecological configurations: first, rainforest habitats with a low degree of human impact, second, steep areas, and third, areas with high prevalence of hunting taboos and low degree of human impact. The largest chimpanzee populations are nowadays found under the third social-ecological configuration, even though most of these areas are not officially protected. Most commonly chimpanzee conservation has been based on exclusion of threats by creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 71 publications
0
40
0
6
Order By: Relevance
“…We then extracted 20 predictor variables for each transect using publicly available satellite and aggregated householdsurvey data which approximate known drivers of chimpanzee density including both environmental variables and anthropogenic pressure (details in table S2 and table S3). We originally started with a model comprising the same predictors used in an earlier study to identify drivers of chimpanzee densities (Heinicke et al 2019), but the initial evaluation of the derived density distribution revealed an underestimation of chimpanzee densities for protected areas. We therefore added 'protected area' as a binary predictor, meaning whether the midpoint of a transect was within the boundaries of a protected area designated as 'national park' or IUCN category I or II based on data from the World Database of Protected Areas (UNEP-WCMC and IUCN 2017).…”
Section: Modeling Chimpanzee Density Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…We then extracted 20 predictor variables for each transect using publicly available satellite and aggregated householdsurvey data which approximate known drivers of chimpanzee density including both environmental variables and anthropogenic pressure (details in table S2 and table S3). We originally started with a model comprising the same predictors used in an earlier study to identify drivers of chimpanzee densities (Heinicke et al 2019), but the initial evaluation of the derived density distribution revealed an underestimation of chimpanzee densities for protected areas. We therefore added 'protected area' as a binary predictor, meaning whether the midpoint of a transect was within the boundaries of a protected area designated as 'national park' or IUCN category I or II based on data from the World Database of Protected Areas (UNEP-WCMC and IUCN 2017).…”
Section: Modeling Chimpanzee Density Distributionmentioning
confidence: 99%
“…Chimpanzees in the Fouta Djallon and adjacent areas appear to be a large population characterized by savanna-mosaic habitat. Despite challenging ecological conditions (Wessling et al 2018), chimpanzees persist here at high densities due to relatively low levels of anthropogenic threats and a high prevalence of hunting taboos (Boesch et al 2017, Heinicke et al 2019. Chimpanzees in the second largest population live in a habitat mostly characterized by rainforest.…”
Section: Implications For Western Chimpanzee Conservationmentioning
confidence: 99%
“…Chimpanzees live in a diversity of habitat types including mosaics of forests and agricultural areas (Hockings et al, ). They are able to persist in areas where hunting pressure is low, usually because local residents have long‐held traditions of not hunting chimpanzees (Boesch et al, ; Heinicke et al, ; Kormos et al, ). Although the effectiveness of conservation activities outside protected areas is under‐studied (Junker et al, ), it is recognized that measures such as reducing hunting pressure are essential (Kühl et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The area selection was based on estimated chimpanzee density distribution that was recently modeled across its entire range using 20 social and ecological factors, including habitat, climate, threats to chimpanzees such as forest loss and human activities, and factors having a positive effect on chimpanzee densities such as protected areas, prevalence of hunting taboos, and steepness of terrain (Heinicke et al, ). This data layer has a spatial resolution of half a minute (of a longitude/latitude degree, approximately 0.9 × 0.9 km) and is available via the IUCN SSC A.P.E.S.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation